Landasan Epistemologis Belajar dalam Al-Qur’an dan Hadis: Analisis Prinsip Pendidikan Islam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The integration of Western psychology and Islamic perspectives has become a significant issue in the development of contemporary knowledge and education. The rapid advancement of modern psychology requires synthesis with Islamic epistemology to provide a more contextual response to academic and practical needs, particularly in the areas of education, counseling, and character development. This article aims to address the research question: What are the trends in integrating Western psychology and Islamic perspectives in recent literature, and what are their implications for the theory and practice of Islamic education? This study employs a qualitative approach through a literature review method. Articles were collected via Google Scholar and Publish or Perish using the keywords “integration of psychology” AND “Islamic education.” From an initial pool of 40 articles, the screening process yielded 5 articles that met the criteria of publication year (2021–2025), topical relevance, and open access availability. The review reveals three main themes: (1) epistemological integration emphasizing the Islamization of knowledge; (2) the application of Islamic psychology in education, counseling, and curriculum development; and (3) conceptual and practical challenges in linking Western psychology with Islamic paradigms. This synthesis highlights the importance of integrative frameworks to enhance the relevance of Islamic psychology in academic and social contexts. Future studies should broaden empirical methodologies and further develop cross-disciplinary applied models.